A facile method for pre-insertion of cations and structural water in preparing durable zinc storage vanadate cathodes. Issue 30 (14th July 2022) - Wang, Yujian; Wang, Shuying; Yang, Linyu; Zhao, Fengjun; Li, Haibing
Abstract : Na2 V6 O16 ·1.96H2 O and K2 V6 O16 ·2.13H2 O nanorods are prepared by a facile stirring method at room temperature as cathodes for zinc ion batteries. Abstract : For improving the overall energy storage performance of aqueous zinc-ion battery (ZIB) systems, it is important to identify new cathode materials with superior characteristics. Along these lines, in this work, Na, K, and structural water were pre-inserted in vanadium oxide via a simple solution reaction method at room temperature. More specifically, Na2 V6 O16 ·1.96H2 O (NVO) and K2 V6 O16 ·2.13H2 O (KVO) nanorods were successfully prepared using CH3 COONa and CH3 COOK, respectively, and commercial V2 O5 powder as starting materials. The NVO and KVO nanorods exhibited high Zn 2+ storage ability; while the specific capacity of the NVO cathode reached 366.8 mAh g −1 at 0.3 A g −1, its capacity retention was 86.6% after 1000 consecutive cycles at 3 A g −1, and the KVO cathode also showed impressive performance. NaV3 O8 and KV3 O8 were prepared for comparison by annealing NVO and KVO at high temperatures. The comparison of their cycling stability, Zn 2+ diffusivity coefficients, and electronic conductivity with the same characteristics of both NVO and KVO cathodes demonstrated that the presence of structural water had a positive impact on the electrochemical performance of the prepared materials. The high performance of NVO and KVO is mainly attributed to the synergistic effect between structural water and metal ions.